(1)-3a^2b+6ab (2)(x^2-2x)^2+2(x^2-2x)+1 (3)(m+n)(m-n)-(1-2n)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 01:26:09
(1)-3a^2b+6ab (2)(x^2-2x)^2+2(x^2-2x)+1 (3)(m+n)(m-n)-(1-2n)
(1)-3a^2b+6ab (2)(x^2-2x)^2+2(x^2-2x)+1 (3)(m+n)(m-n)-(1-2n)
(1)-3a^2b+6ab (2)(x^2-2x)^2+2(x^2-2x)+1 (3)(m+n)(m-n)-(1-2n)
(1)-3a²b+6ab
=-3ab(a-2b)
(2)(x²-2x)²+2(x²-2x)+1
=[(x²-2x)+1]²
=[(x-1)²]²
=(x-1)
(3)(m+n)(m-n)-(1-2n)
=m²-n²-1+2n
=m²-(n²-2n+1)
=m²-(n-1)²
=(m+n-1)(m-n+1)
(1)-3a^2b+6ab=-3ab(a-2)
(2)(x^2-2x)^2+2(x^2-2x)+1=[(x^2-2x)+1]^2=(x-1)^4
(3)(m+n)(m-n)-(1-2n)=m^2-n^2+2n-1=m^2-(n-1)^2=(m+n-1)(m-n+1)
1)-3a²b+6ab
=3ab(2-a)
(2)(x²-2x)²+2(x²-2x)+1
= (x²-2x+1)²
(3)(m+n)(m-n)-(1-2n)
=m²-n²-1+2n
=m²-(n²-2n+1)
=m²-(n-1)...
全部展开
1)-3a²b+6ab
=3ab(2-a)
(2)(x²-2x)²+2(x²-2x)+1
= (x²-2x+1)²
(3)(m+n)(m-n)-(1-2n)
=m²-n²-1+2n
=m²-(n²-2n+1)
=m²-(n-1)²
=(m+n-1)(m-n+1)
有不明白的可以追问!
希望我的回答对你有
收起
过来灌灌水吧,有奖励哦